Dimensi Religius Di Balik Tradisi Dapur Bersih Dusun Gombong, Desa Paripurno, Magelang: Respon terhadap QS. Al- A’raf Ayat 56 dan QS. Ar-Rum Ayat 41 - Akhmad, Nur; Mustofa, Ahmad; Rosowulan, Titis (Bayani, 2025)
This study explores the religious dimensions embedded within the "Clean Kitchen" tradition of Dusun Gombong, Paripurno Village, Magelang, through the lens of Living Qur’an. The tradition, rooted in communal practices of cleanliness, reflects internalized Qur’anic values such as purity (?ah?rah), gratitude, and divine blessing. The research aims to analyze how these spiritual principles—particularly those found in QS. Al-A’raf: 56 and QS. Ar-Rum: 41—are interpreted and manifested in daily domestic rituals. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation. Theoretical frameworks of Living Qur’an and Environmental Theology guide the analysis, emphasizing the dynamic interplay between sacred texts and lived realities. Findings reveal that the Clean Kitchen tradition serves as a spiritual practice that fosters ecological awareness, ethical responsibility, and community empowerment. It demonstrates how Islamic teachings can be actualized in everyday life, contributing to sustainable environmental stewardship and holistic religious expression.